COMPARISON OF INTER-MAXILLARY FIXATION SCREWS WITH ARCH BARS FOR THEIR EFFECTIVENESS IN ESTABLISHING OCCLUSION BEFORE OPEN REDUCTION AND INTERNAL FIXATION IN MANDIBULAR FRACTURES - Mairaj, Wajid; Shah, Irfan; Khan, Muhammad Nazeer; Khan, Ali Akhtar; Babar, Adnan; Mahmood, Saad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the effectiveness of inter-maxillary screws in establishing occlusion over arch bars and to determine possible complications associated with both techniques. Study Design: Comparative prospective study. Place and Duration of Study: Department of Oral & Maxillofacial Surgery, Armed Forces Institute of Dentistry, Rawalpindi from Jul 2018 to Jul 2019. Methodology: Forty-four patients having mandibular fractures were selected. Participants were divided into group A (arch bar) and group B (inter-maxillary screws). Randomization was done through lottery method. Patients with permanent dentition and unilateral fractures in dentate area of the mandible were included in the study. Glove punctures, time taken for establishing intermaxillary fixation, stability of occlusion, hardware tolerability, oral hygiene and associated complications were recorded at per-op and 04 weeks follow up. Results: Glove puncture was more frequent in arch bar group 13(65%) than intermaxillary screw group 3 (13%) [p.001]. The time needed for establishing intermaxillary fixation with intermaxillary screws was less than that of arch bar group (p<0.001). The hardware tolerability (p=0.001) and oral hygiene (p=0.001) were statistically better in intermaxillary screw group than arch bar group. The associated complications were statistically different between the two methods of intermaxillary fixation (p=0.034). Conclusion: Intermaxillary screws are more effective than arch bar in establishing intermaxillary fixation.